Comparison between the formula 1/2ABC and 2/3Sh in intracerebral parenchyma hemorrhage. (1st May 2013) - Yan, Jing; Zhao, Kaijun; Sun, Jialan; Yang, Wanlin; Qiu, Yulan; Kleinig, Timothy; Fu, Yi; Chen, Shengdi
<x xml:space="preserve">Abstract</x> Background and purpose: The 1/2ABC formula is the method most commonly used in clinical practice to rapidly estimate intracerebral hemorrhage (ICH) volume. We aimed to compare this method with the alternative '2/3Sh' formula for both regularly and irregularly-shaped hematomas. Methods: Computed tomography (CT) images from 344 ICH patients (median volume: 16·66 ml) were retrospectively reviewed. According to the maximum slice, the shape was classified into regular or irregular (multilobular, conical, and other). Volumes as determined by the 1/2ABC and 2/3Sh formulas were compared against the gold standard, computer-assisted planimetry, for various hematoma shapes. Results: With the 1/2ABC method, errors were seen non-significantly more frequently for irregularly-shaped hematomas [OR: 2·85 (95% CI: 0·65-12·50)]. The 1/2ABC method misclassified a greater proportion of hematomas as greater or less than 30 ml in volume: 7·0% (95% CI: 6·0-9·9%). Both the 1/2ABC and 2/3Sh formulas correlated well with gold standard (correlation coefficients >0·9 for each shape). While there was no statistically significant measurement error bias for either method, the 95% confidence intervals of the limit of agreement for 2/3Sh were tighter: −0·22 ml (−4·7-4·25 ml) versus 2·50 ml (−10·35-15·34 ml). Measurement errors were significantly greater with the 1/2ABC method, for both regular and irregular hematomas [1·17 ml (0·48-2·83 ml) versus 0·88 ml (0·42-1·68 ml) and 2·65 ml (1·07-5·88 ml) versus 0·99 ml (0·47-2·28 ml); P<0·05, respectively], although the magnitude of error would only rarely be clinically relevant for regular hematomas. Errors were most evident in assessing multilobular-shaped hematomas [6·49 ml (3·35-13·98 ml) versus 1·86 ml (0·96-9·94 ml); P<0·001]. Conclusions: The 2/3Sh formula leads to fewer clinically-relevant hematoma volume misclassifications than the 1/2ABC formula, and is particularly superior in estimating volumes of irregularly-shaped hematomas.